Konsep Jiwa Perspektif Ibnu Sina - Debi Putri Serena; Siti Umi Hani; Bunga Septria Vionita; Badru Sohim (Media: Jurnal Filsafat dan Teologi, 2023)
The purpose of this essay is to clarify Ibn Sina's views on the spirit and its connection to the body. A qualitative approach is used in this research to conduct a review of the literature. This study's methodology is an investigation into Islamic literacy using both main and secondary data sources. The body and the soul are different entities or made up of diverse materials, according to Ibn Sina. The soul is not gone when the body is destroyed. The soul lasts forever. Even though the body and the soul are made up of distinct substances, they are both interdependent. It is impossible to separate the soul from the body. The tendency of western philosophical thought toward dualism of soul and body is overcome by Ibn Sina's idea. The relationship between both the body and the spirit demands.